Differentially Expressed MiRNAs of Goat Submandibular Glands Among Three Developmental Stages Are Involved in Immune Functions - Wang, Aili; Ji, Zhibin; Xuan, Rong; Zhao, Xiaodong; Hou, Lei; Li, Qing; Chu, Yunpeng; Chao, Tianle; Wang, Jianmin (Frontiers in Genetics, 2021)
Submandibular glands(SMGs) are one of the primary components of salivary glands in goats. The proteins and biologically active substances secreted by the SMGs change with growth and development. Our previous studies showed that most of the differentially expressed genes in the SMGs of goats at different developmental stages are involved in immune-related signaling pathways, but the miRNA expression patterns in the same tissues are unknown. The aim of this study was to reveal the expression profile of miRNAs at three different developmental stages, detect differentially expressed miRNAs (DE miRNAs) and predict disease-related DE miRNAs. SMG tissue samples were collected from groups of 1-month-old kids, 12-month-old maiden goats and 24-month-old adult goats (3 samples from each group), and high-throughout transcriptome sequencing was conducted. A total of 178, 241 and 7 DE miRNAs were discovered between 1-month-old kids and 12-month-old maiden goats, between 1-month-old kids and 24-month-old adult goats, and between 12-month-old maiden goats and 24-month-old adult goats, respectively. Among these DE miRNAs, 88 DE miRNAs with medium or high expression levels (TPM ≥ 50) were classified into 5 expression pattern clusters. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses indicated that some of the predicted target genes of the DE miRNAs in the 5 clusters were enriched in disease-related GO terms and pathways. MiRNA target genes in significant pathways were significantly enriched in Hepatitis B (FDR= 9.03E-10) and Pathways in cancer (FDR=4.2E-10). Further analysis was performed with a PPI network, and 10 miRNAs were predicted to play an important role in the occurrence and prevention of diseases during the growth and development of goats.